STRESS, DEPRESSION AND ANXIETY LEVELS AMONG PARENTS OF “LEARNING FROM HOME” DURING COVID-19 PANDEMIC - Denny Anggoro Prakoso; Alya’ Laudza; Yusuf Oka Mahendra; Naufal Hanif; Fitria Nurul Hidayah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Abstract: One of the consequences of the Covid-19 pandemic is the adaptation process and changes in the education process. During the Covid-19 crisis, the Indonesian Ministry of Education and Culture implemented a policy to aid in preventing Covid-19 spread through regulations governing the implementation of